7 Should the governments fund assisted reproductive technologies?. Issue Volume 24:Issue Supplement 1(2019) (July 2019) - O'Nolan, Gerald; Long, Jean; Keane, Martin; Farragher, Louise
Abstract : Objectives: Access to assisted reproductive technologies (ART) for those seeking treatment is dependent on their ability to afford such treatments. A combination of out-of-pocket payment, public funding and the availability of health insurance determines the uptake of ART services in most countries. The variation between countries ranges from public funding with some limitations and/or small out-of pocket payments (Australia, Belgium, France, Slovakia, Slovenia, Spain and Israel) to no funding of any kind (Malta, Switzerland and the USA). In Ireland, such technologies have not yet been subject to government regulation or funding. The Irish Government requested the Health Research Board to investigate the costs and benefits associated with the public funding of ART for the funder, provider, and service user. Method: The methods employed to undertake this work followed the principles of a systematic review, including searching, screening, applying inclusion/exclusion criteria, data extraction, quality appraisal, and synthesis. Results: A benefit to public funding for ART in the literature reviewed includes improving access to treatment by reducing out-of-pocket payments. Clinical benefits can also reduce the pressure on public spending. In some countries, public funding is contingent on patients and clinicians agreeing to restrict the number of embryos transferred in one cycle: single embryo transfer (SET). Where SET has occurred, there has been a significant reduction in multiple pregnancies without causing a decrease in cumulative pregnancy rates, as well savings to the public health system. The literature outlines inferred benefits to wider society when public funding for ART is approved. In some countries, ART is seen as a social investment towards arresting the declining fertility rate, and overall future revenue receipts. Research indicates for women aged over 40 years, live births are substantially less likely following ART treatments and the financial cost of achieving a live birth is substantially more. Conclusions: Every country has a different approach to ART and the likely funding mechanism may emerge through trial and error. State funding with regulation can provide a cost-effective solution for patients who are subfertile and for wider society.